Swamp Thing the dead don't sleep - Wein, Len 1948-2017; Jones, Kelley 1962- (DC Comics, 2016)
"Swamp Thing returns in an all-new graphic novel written by his co-creator, legendary writer Len Wein and illustrated by the critically acclaimed horror master, Kelley Jones! Swamp Thing has received an ominous warning, and now he finds himself under attack from the forces of dark magic. These are more than just your average monsters...and there's something much worse looming on the horizon for Alec Holland! An old friend appears in the swamp with an unbelievable proposition for Swamp Thing: using a dark spell, it might be possible for the Avatar of the Green to return to his human form as Alec Holland and regain his old life. But all magic has a cost...will Swamp Thing get everything he has ever wanted, or discover the consequences of leaping before you look? With an all-star creative team, the Avatar of the Green returns to his horror roots in SWAMP THING: THE DEAD DON'T SLEEP"...